Ottoman Bazaars in Anatolia and the Balkans: An Overview of Influences in Defining Spatial and Architectural Qualities (Prostor, 2024)
Bazaars were spaces that formed the center of the cities during the Ottoman period, had a certain order, and were shaped spatially and architecturally depending on the geographical-topographical characteristics and commercial potential of each city. Proximity to the citadels, connection with city gates and main roads, relations with Friday mosque and other public buildings in the city were the main factors shaping the bazaar spatially. In bazaars, where bedesten and khans, and in some cases covered bazaar-arastas, appeared on a building scale, shops that lined on open or covered streets formed the architecture of the bazaar. In addition to these, the sovereignty and order established by the state over trade during the Ottoman period, the institution of waqf, and the guilds of tradesmen also played a decisive role in the bazaar. With the bazaars examined, it is concluded that while administrative and commercial influences in the shaping of bazaars in Anatolian and Balkan cities during the Ottoman period created bazaar spaces with similar qualities, urban inputs led to the differentiation of bazaars in terms of scale, spatial and architectural qualities.